Real-world objects are more memorable than photographs of objects - Snow, Jacqueline C.; Skiba, Rafal M.; Coleman, Taylor L.; Berryhill, Marian E. (Frontiers in Human Neuroscience, 2014)
Research studies in psychology typically use two-dimensional (2D) images of objects as proxies for real-world three-dimensional (3D) stimuli. There are, however, a number of important differences between real objects and images that could influence cognition and behavior. Although human memory has been studied extensively, only a handful of studies have used real objects in the context of memory and virtually none have directly compared memory for real objects versus their 2D counterparts. Here we examined whether or not episodic memory is influenced by the format in which objects are displayed. We conducted two experiments asking participants to freely recall, and to recognize, a set of 44 common household objects. Critically, the exemplars were displayed to observers in one of three viewing conditions: real-world objects, colored photographs, or black and white line drawings. Stimuli were closely matched across conditions for size, orientation, and illumination. Surprisingly, recall and recognition performance was significantly better for real objects compared to colored photographs or line drawings (for which memory performance was equivalent). We replicated this pattern in a second experiment comparing memory for real objects versus color photos, when the stimuli were matched for viewing angle across conditions. Again, recall and recognition performance was significantly better for the real objects than matched color photos of the same items. Taken together, our data suggest that real objects are more memorable than pictorial stimuli. Our results highlight the importance of studying real-world object cognition and raise the potential for applied use in developing effective strategies for education, marketing, and further research on object-related cognition.